Analisis Faktor-Faktor Pembentuk Keputusan Pembelian Konsumen Pada Merek Kosmetik Lokal (Pixy) di Semarang - Khairani, Indah; Pradekso, Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Doing product innovation and rebanding is one of the ways companies stay in the market. The high increase in the cosmetic industry cosmetic companies lead the company to be creative and keep ahead in the eyes of consumers. Pixy as one of the cosmetic brands rebranding and innovating products with the aim of making consumers more familiar with the Pixy brand. However, the rebranding that Pixy did did not have a good effect on the percentage of Top Brand Index data. On the contrary, Pixy actually experienced a decline in Top Brand Index data. So, the purpose of this research is to find out what factors can influence consumers in buying cosmetic products. Referring to the purpose of these objectives, researchers gathered various kinds of basic concepts about the factors that influence consumers in purchasing decisions and found 20 factors to be analyzed further. This research is a quantitative research with explorative type. This research was conducted on 100 respondents who knew the Pixy cosmetics brand and based in Semarang. The analysis used in this research is factor analysis with the results of data processing using IBM SPSS through several stages of data processing. Of the 20 factors that influence consumer purchasing decisions analyzed, five new factors are formed consisting of product quality factors, external factors, perception factors, material factors, brand ambassador factors, and word of mouth factors. The conclusion of this study is from the silence of new factors that formed, it was found that the product quality factor (component 1) was the most appropriate factor to summarize the 20 existing factors.